Cultural events as a method for creating a new future for museums - Daria E. Jaremen; Andrzej Rapacz (Tourism, 2018)
In the situation of insufficient subsidies for the substantive activities of museums, primarily the ones funded by the local governments, as well as low attendance of visitors, not really interested in the traditional offer of such institutions, there is an urgent need to extend it with additional elements corresponding to the expectations of a contemporary client. The observation of the thriving museums in Poland and worldwide indicates that cultural events represent such an attractive component which expands the museum offer. The article presents an attempt of explaining the role of cultural events in developing a museum product based on the analysis of a specific case of the Municipal Museum Gerhart Hauptmann’s House in Jelenia Góra-Jagniątków.